Emergency Medical Services Calls for Service at Adult Detention Centers: A Descriptive Study - Jeffrey N. Wood; Aaron B. Klassen; Matthew D. Sztajnkrycer (Western Journal of Emergency Medicine)
Introduction: Incarcerated individuals represent a vulnerable sector of society, with a disproportionate burden of substance use, mental health problems, and chronic illness. The purpe of this study was to perform a descriptive analysis of emergency medical services (EMS) response to detention facilities. Methods: We conducted a retrospective review of Mayo Clinic Ambulance Service ground EMS emergency (9-1-1) calls for service to nine detention centers within the service area occurring between January 1, 2002–December 31,2021. We excluded calls to a 10 th detention center, the Federal Medical Center – Rochester, due to the unique nature of this facility. Additional exclusion criteria included non-emergency calls and lack of patient care narratives within the patient care report. We analyzed data using descriptive statistics, chi-square, and the Student t-test. This study was reviewed and approved by the Mayo Clinic Institutional Review Board. Results: During the study period, 3,114/1,231,853 (0.25%) service requests to detention facilities occurred. After accounting for exclusion criteria, the final sample size consisted of 2,034 patients. Average patient age was 40.2 ± 13.3 years of age, compared with 54.0 ± 25.9 years of age for non-detention center calls ( P < 0.001). The majority (80.8%) of patients were male. Mean scene time was 14:13 ± 7:49 minutes, compared with 12:04 ± 12:27 minutes ( P < 0.01) for non-detention center calls. The most common complaints were medical, behavioral emergencies, cardiac, and trauma. Obstetrics requests accounted for 5.8% of calls for female patients. Most calls (91.3%) to detention centers involved incarcerated individuals, with the remainder representing facility staff (1.5%), visitors (0.5%), and undetermined (6.7%). Nearly 4% of patients refused treatment; 48.9% of these patients were still transported. Consent for treatment/transport by the patient was documented in 6.1% of charts. Conclusion: Recognizing the retrospective, single-agency nature of this study, we found that calls to detention facilities within our 9-1-1 service area predominantly involved incarcerated individuals. Consent for treatment/transport was not documented in most EMS encounters. Further study is needed to better understand the healthcare needs of these patients, including ability to consent.